2015
DOI: 10.7150/jca.11689
|View full text |Cite
|
Sign up to set email alerts
|

Annexin A3 Is a Potential Predictor of Platinum Resistance in Epithelial Ovarian Cancer Patients in a Prospective Cohort

Abstract: Epithelial ovarian cancer (EOC) is the leading cause of death among gynecological malignancies and is rarely cured in the recurrent setting, mainly because of progressive chemoresistance, especially platinum resistance. In our previous studies, the platinum-resistance-related protein, annexin A3, was selected by comparative proteomics. In this study, we detected serum annexin A3 levels using a self-developed chemiluminescence immunoassay kit in a prospective EOC patient cohort. We also evaluated the capacity o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…For instance, the C118T and C8092A polymorphisms in ERCC1 have been strongly correlated with objective response rate and overall survival ( 89 ). Similarly, the levels of annexin A3 in the peripheral blood may be a potential predictor for platinum resistance in ovarian cancer ( 90 ). Although molecular markers have the potential to predict therapy response, rigorous validation in large patient cohorts would truly bring out the benefits of such predictions.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, the C118T and C8092A polymorphisms in ERCC1 have been strongly correlated with objective response rate and overall survival ( 89 ). Similarly, the levels of annexin A3 in the peripheral blood may be a potential predictor for platinum resistance in ovarian cancer ( 90 ). Although molecular markers have the potential to predict therapy response, rigorous validation in large patient cohorts would truly bring out the benefits of such predictions.…”
Section: Discussionmentioning
confidence: 99%
“…[38][39][40][41] More relevant to the sepsis profiling data presented and discussed here, mechanistic studies point to a role played by ANXA3 in promoting cancer growth and metastasis. [42][43][44][45] Notably, a recent study also reported benefits of anti-ANXA3 monoclonal antibodies in a preclinical mouse model of HCC. 45 Although ANXA3 expression in many cancer cells seems to correlate directly with the rate of cellular proliferation, 47,48 the underlying mechanism(s) are undefined.…”
Section: Additional Reference Datasets Inform On Anxa3 Restriction Anmentioning
confidence: 98%
“…Exosomal proteins can also represent important biomarkers for the evaluation of efficacy of therapies. Thus, annexin A3 can be employed for early detection of the resistance to platinum-based therapy in ovarian cancer patients [135,136].…”
Section: Extracellular Vesicles As Biomarkers-new Diagnostic Toolsmentioning
confidence: 99%